Morphology and Anatomy of Andong Plant Cultivars (Cordyline fruticose (L.) A. Chev.) As Plants that Adsorb and Absorb Motor Vehicle Lead Emissions - Taihuttu, Hermina Neltje; Ariffin, Arifin; Nihayati, Ellis; Sitawati, Sitawati (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Motorized vehicles contribute to air pollution containing lead. The ability of leaves to absorb pollutants is influenced by leaf characteristics. Stomata are one of the entry points for pollutants, especially from the air, such as lead. The research aims to: obtain information about morphological and anatomical characters and compare between cultivars. Using exploration and characterization methods. Leaf morphology, based on observations of color, shape and size, is different Winnie Gold cultivar has length, L/W, width, Miss Andrea cultivar has higher width, lower L/W. The H. Bonsai cultivar has lower length, width, leaf area than the other 5 cultivars.The anatomy of andong leaves is based on observations of stomata, the same, hypostomatic/abaxial and actinocytic types. The Fire Brand cultivar has a higher number, density, lower width, the H. Bonsai cultivar has a higher length, higher width, lower number, density, the Miss Andrea cultivar has a lower length than the other 5 cultivars.